Nomogram model using serum Club cell secretory protein 16 to predict prognosis and acute exacerbation in patients with idiopathic pulmonary fibrosis - Yaqiong Tian; Xuan Zhou; Mi Tian; Lijun Ren; Ruyi Zou; Hanyi Jiang; Miaomiao Xie; Mei Huang; Jingjing Ding; Yin Liu; Jingyu Chen; Min Cao; et al. (European Journal of Medical Research)
Abstract Background Idiopathic pulmonary fibrosis (IPF) is a progressive fibrotic lung disease with poor prognosis, nomogram model for its prognosis and acute exacerbation was constructed. Methods Two hundred and sixty eight patients with IPF were grouped with different severity according to fibrosis area, serum Club cell secretory protein 16(CC16) was compared between these groups. All patients were randomly divided into training and testing sets. COX regression and LASSO algorithm were used to screen featured characteristics. Then nomogram models were constructed, ROC curve, calibration curve and decision curve analysis(DCA) were conducted to evaluate the performance of model. Expression of CC16 were detected in fibrotic human lung tissues, bronchoalveolar lavage fluid (BALF) and Bleomycin(BLM)-treated mouse lung tissues and serums. Results Serum CC16 gradually increased with the severity of fibrosis, and was especially high in AE-IPF group. CC16 and diffusion capacity for carbon monoxide (DLCO) were screened as characteristic variables to construct nomogram model for IPF prognosis. The survival was significantly lower in high-risk group scored by the model. The area under ROC curves(AUCs) for 1-year and 2-year mortality prediction were 0.866 and 0.916, respectively. This model performed better than gender-age-physiology (GAP) index for predicting 2-year and 3-year mortality. Another nomogram model for acute exacerbation of IPF based on CC16, Krebs von den Lungen-6(KL-6) and DLCO was developed, the AUC was 0.815. Expression of CC16 obviously up-regulated in fibrotic lung tissues, BALF and BLM-treated mice lung tissues and serums. Conclusions The nomogram model based on CC16 performed good predictive ability for prognosis and acute exacerbation of IPF.